(untitled) (Revista Internacional de Formação de Professores, 2018)
This article aims to show the importance of the discussion about the values and purposes of education that guide both the content of school curricula and the pedagogical practices that are developed in schools. Based on authors who support this discussion, two initial questions were posed: what goals do we intend to achieve through the action of the school; and whether this discussion is present in school. To develop the theme, we first sought the sense of education and how the school places itself in this context, emphasizing that the current educational process becomes increasingly complex, requiring a curriculum that fades from the merely reproducible and a set of pedagogical practices equally complex. Finally, the text emphasizes the importance of answering three fundamental questions: what we value for the educational process; why we wish to form, in view of the proposed ends; and how, what pedagogical practices we will recover or develop to achieve those ends.